Breast tumour size as a predictor of hemostatic system status and endothelial function in dogs - Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Білий, Дмитро Дмитрович; Rublenko, M. V.; Рубленко, М. В.; Samoiluk, V. V.; Samoylyuk, Vyacheslav; et al. (Oles Honchar Dnipropetrovsk National University, 2019)
The high level of morbidity of dogs from mammary gland tumours and deficiencies in the pathogenesis give relevance to study of the disorders of the hemostatic system for predicting the neoplasia process. Our research concerned the determination of markers of the hemostatic system and endothelial function at different sizes (≤ 2, 5–7 and >10 cm) of benign (n = 28) and malignant (n = 27) breast tumours in dogs, taking into account their histological structure. The progression of the tumour process was accompanied by a 1.24–1.81 times increase in the fibrinogen content in the benign forms and 1.39–2.38 times in malignant against the background of progressive excess accumulation of soluble fibrin. The results of coagulation tests indicate that the increase in blood coagulation, which correlates with the magnitude of tumours, occurred mainly externally. In malignant neoplasms reliable, compared to clinically healthy dogs, reduction of total fibrinolytic activity occurred due to deficient inhibition of tissue plasminogen activator by 1.62–2.03 times. Increase in the size of benign neoplasms was accompanied by increased activity of the α1inhibitor of proteinases, and in malignant – only in tumours of the size of 5–7 cm, against the background of its decrease in dogs with small and giant neoplasia. The progression of the disease was characterized by an increase in the content of α2-macroglobulin in benign lesions from 1.19–1.24 times, malignant – from 1.25–2.03 times. At the same time, there was a deepening of oxidative stress, as evidenced by the excess accumulation in the blood of malondialdehyde by 1.29–1.70 times in benign tumours, and 1.58– 2.73 times in malignant. Regardless of the pathomorphologic form, the magnitude of the neoplasia foci is directly correlated with excess accumulation of nitric oxide and the level of hypoproteinemia, and vice versa – the content of ceruloplasmin. Further research should be undertaken to study the hemostatic status in certain nosological forms of breast tumours in dogs, which will improve the diagnosis and development of effective treatment protocols. Високий рівень захворюваності собак на пухлини молочних залоз та дефіцит патогенезу надають значення вивченню порушень системи гемостазу для прогнозування процесу новоутворення. Наше дослідження стосувалось визначення маркерів гемостатичної системи та функції ендотелію при різних розмірах (≤ 2, 5–7 та> 10 см) доброякісних (n = 28) та злоякісних (n = 27) пухлин молочної залози у собак, беручи до уваги враховувати їх гістологічну структуру. Прогресування пухлинного процесу супроводжувалось збільшенням вмісту фібриногену в доброякісних формах у 1,24–1,81 рази та злоякісних у 1,39–2,38 рази на тлі прогресивного надлишкового накопичення розчинного фібрину. Результати тестів на згортання крові вказують на те, що збільшення згортання крові, яке корелює з величиною пухлин, відбувалися переважно зовні. У злоякісних новоутвореннях, достовірних порівняно з клінічно здоровими собаками, зниження загальної фібринолітичної активності відбувалося через недостатнє інгібування тканинного активатора плазміногену в 1,62–2,03 рази. Збільшення розмірів доброякісних новоутворень супроводжувалося посиленням активності α1-інгібітора протеїназ, а злоякісних - лише при пухлинах розміром 5–7 см, на тлі його зменшення у собак з невеликою та гігантською неоплазією. Прогресування захворювання характеризувалось збільшенням вмісту α2-макроглобуліну у доброякісних ураженнях з 1,19–1,24 разу, злоякісних - з 1,25–2,03 разів. У той же час відбулося поглиблення окисного стресу, про що свідчить надлишкове накопичення в крові малонового диальдегіду в 1,29-1,70 разів при доброякісних пухлинах і в 1,58-2,73 разів при злоякісних. Незалежно від патоморфологічної форми, величина вогнищ неоплазії безпосередньо корелює з надлишковим накопиченням оксиду азоту та рівнем гіпопротеїнемії, і навпаки - вмістом церулоплазміну. Подальші дослідження слід проводити для вивчення гемостатичного статусу при деяких нозологічних формах пухлин молочної залози у собак, що покращить діагностику та розробку ефективних протоколів лікування.
Розмір пухлини молочної залози як предиктор стану гемостатичної системи та функції ендотелію у собак
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384 Самойлюк Вячеслав Володимирович https://orcid.org/0000-0001-8400-8904 Масліков Сергій Миколайович https://orcid.org/0000-0003-1353-3968
Keywords: hypercoagulation; гіперкоагуляція; neoplasms; новоутворення; hemostasis balance; баланс гемостазу; endothelial function; функція ендотелію; neoplasia size; розмір новоутворення